2015
DOI: 10.1063/1.4918412
|View full text |Cite
|
Sign up to set email alerts
|

A validation of the fibre orientation and fibre length attrition prediction for long fibre-reinforced thermoplastics

Abstract: Abstract. To improve the mechanical performance of polymeric parts, fibre reinforcement has established in industrial applications during the last decades. Next to the widely used Short Fibre-reinforced Thermoplastics (SFT) the use of Long Fibre-reinforced Thermoplastics (LFT) is increasingly growing. Especially for non-polar polymeric matrices like polypropylene (PP), longer fibres can significantly improve the mechanical performance. As with every kind of discontinuous fibre reinforcement the fibre orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This mechanism of fiber pull‐out might occur particularly for longer fibers and would explain the increase of residual fiber length in the molded part towards the end of the flow path. While similar trends were reported in other studies , a thorough study is required to understand and explain the observed phenomenon.…”
Section: Discussionsupporting
confidence: 78%
“…This mechanism of fiber pull‐out might occur particularly for longer fibers and would explain the increase of residual fiber length in the molded part towards the end of the flow path. While similar trends were reported in other studies , a thorough study is required to understand and explain the observed phenomenon.…”
Section: Discussionsupporting
confidence: 78%
“…Works dealing with the experimental analysis and modelling of glass FB in injection moulding or extrusion supported this assumption. 2,3,[5][6][7]16,[19][20][21] For this reason, only the diameter in the as-received pellets was measured in this work.…”
Section: Quantification Of Fibre Length Attritionmentioning
confidence: 99%
“…Many works have dealt with FB of polymer composites processed by injection moulding. 1,2,[5][6][7] Phelps et al's model 6 and its implementation in mould filling simulators, that is Moldflow and Moldex3D, is probably the most relevant approach in this topic. It is a statistical model, which describes the probability of a fibre breaking due to buckling and shearing forces in a flow field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively one could use a simulation of the intended production process (CFD simulation of polymer melt [21]) to predict a geometry for the system. Such a simulation would respect the influence of the production process on the geometry, but it requires a lot of material properties, and Hopmann [13] showed, that default values provided by typical CFD software packages often yield unsuitable results. The most feasible approach is to choose a suitable (parametrized) distribution for the directions of the fibres and adjust the parameters to the composite geometry.…”
Section: Geometrical Composite Modelingmentioning
confidence: 99%